The “New Turkey” Narrative _x000D_ and The Hegemonic Struggle of _x000D_ Justice and Development Party and _x000D_ Erdogan: A Gramscian Perspective _x000D_ (2002-2019) - (:unkn) unknown (My University, 2021)
The production of legitimacy and consent has always been among the main concerns and questions of political science. The political success of Erdoğan and the Justice and Development Party (AK Parti) is based on the progress made in the process of democratization and economic development policies as much as on their ability to align the popular masses with their political orientations and visions. In this perspective, firstly, the narrative of New Turkey presents itself as a discursive and strategic instrument and as a superstructural element. Secondly, this narrative contains ideological, cultural and normative elements in that the AK Parti uses it in its hegemonic struggle against the political and cultural elites of Old Turkey. Indeed, by adopting a perspective of analysis around the narrative of New Turkey, this work aims to focus on the emergence and evolution of this narrative according to the conjonctural and contextual changes. On the other hand, the focus will be on how the political power tries to embody this narrative in political, social and cultural fields through its various actions and policies.

Meşruluk ve rıza üretimi süreçlerinin incelenmesi siyaset biliminin temel araştırma konuların?dan biri olmuştur. Türkiye’de 2002 yılından beri iktidarda olan Adalet ve Kalkınma Partisi (AK _x000D_ Parti) ve lideri Recep Tayyip Erdoğan, bu süre zarfında hem istikrarli bir ekonomik büyümeyi _x000D_ hem de demokratikleşme yönündeki reformları hayata geçirmede önemli başarılar elde et?miştir. AK Parti ve Erdoğan’ın, geniş halk kitlelerini kendi politika hedefleri ve yönelimleriyle _x000D_ ilişkilendirebilmesi de önemli bir başarı olarak görülmektedir. Bu bağlamda, siyasi iktidar “Yeni _x000D_ Türkiye” anlatısını söylemsel ve stratejik bir araç ve üstyapısal bir etken olarak kullanmaktadır. _x000D_ Yeni Türkiye söylemi ve bunun barındırdığı ideolojik, kültürel, normatif öge ve simgeler, Eski _x000D_ Türkiye ve onun elitleriyle girişilen hegemonya mücadelesinde kullanıma sokulmaktadır. Bun?lardan hareketle bu çalışmada, Yeni Türkiye kavramının ortaya çıkış süreci, içeriği ve yaşamış _x000D_ olduğu konjonktürel dönüşümler ele alınacaktır. Bununla birlikte, siyasi iktidarın çeşitli eylem ve _x000D_ politikalarıyla bu söylemi siyasal, sosyal ve kültürel alanlarda nasıl somutlaştırmaya çalıştığına _x000D_ da odaklanılacaktır.
“Yeni Türkiye” Söylemi ve AK Parti ile Erdoğan’ın Hegemonik Mücadelesi: Gramscian Bir Perspektif (2002-2019)